1999
DOI: 10.1023/a:1006120006471
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic cooperation between c-Myc and Bcl-2 in lymph node progression of T1 human breast carcinomas

Abstract: The overexpression of Bcl-2, an anti-apoptotic oncogene, identifies human T1 breast cancer patients who have an increased risk of lymph-node metastasis. We examined in these patients (n = 142) whether the c-Myc oncogene influences metastatic progression in conjunction or not with Bcl-2 expression and the loss of apoptosis in tumors. The association between Bcl-2 and lymph-node metastasis was only significant when c-Myc was concomitantly expressed (chi2 test, p = 0.008). Moreover, very large associations (pOR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Previous studies also suggest that ROCK is implicated in the regulation of c-Myc (25,27,28). c-Myc plays a pivotal role in modulating cell division and transformation (29,30), and clinical studies have shown a strong association between overexpression of c-Myc and tumor metastasis (31)(32)(33). In our study, the c-Myc level was significantly increased in MDA-MB-231 and SUM1315 cells compared with MCF-7 cells in vitro ( Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies also suggest that ROCK is implicated in the regulation of c-Myc (25,27,28). c-Myc plays a pivotal role in modulating cell division and transformation (29,30), and clinical studies have shown a strong association between overexpression of c-Myc and tumor metastasis (31)(32)(33). In our study, the c-Myc level was significantly increased in MDA-MB-231 and SUM1315 cells compared with MCF-7 cells in vitro ( Fig.…”
Section: Resultssupporting
confidence: 76%
“…Many studies have shown that c-Myc is amplified and/or overexpressed in breast cancer (34,45), particularly in late-stage/ high-grade tumors and metastatic tumors (31)(32)(33). Its aberrant expression appears to be a clinical prognostic marker for recurrence and adverse outcomes in breast cancer patients (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Janocko et al (1995) found a preferential sequence for gene amplification in breast cancer, with c-myc most often occurring first, followed by c-erbB-2. Sierra et al (1999) demonstrated in breast cancer patients that Bcl-2 overexpression was strongly associated with lymph node metastasis, but only when c-myc was co-expressed. Caspase 9 is a downstream cofactor in myc-dependent tumourigenesis and progression.…”
Section: Amplification Of C-myc In Relation To Other Oncogenesmentioning
confidence: 99%
“…Aberrant regulation and overexpression of c-Myc are observed in most tumor types, and the c-Myc signaling is believed to play a critical role in oncogenesis (4)(5)(6)(7). A large body of studies have shown that c-Myc is pathologically amplified and/or overexpressed in breast cancers (8,9), particularly in late-stage tumors (10)(11)(12). Its activation seems to be a prognostic marker in predicting recurrence and adverse outcomes in patients with breast cancer (5)(6)(7)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%